PENGEMBANGAN BAHAN AJAR METODOLOGI PEMBELAJARAN BAHASA INDONESIA DI PGMI FITK UIN RADEN FATAH PALEMBANG - Sholikhah, Hani Atus; Handayani, Tutut (Jurnal Ilmiah Bina Edukasi, 2020)
The aims of this study were (1) designing teaching materials "Metodologi Pembelajaran Bahasa Indonesia"; (2) implementing valid operational procedures for teaching materials "Metodologi Pembelajaran Bahasa Indonesia"; (3) carry out practical operational procedures for teaching materials "Metodologi Pembelajaran Bahasa Indonesia", (4) analyze the effectiveness of teaching materials "Metodologi Pembelajaran Bahasa Indonesia". Collecting research data using observation, questionnaires, and interviews. Research and development of teaching materials "Metodologi Pembelajaran Bahasa Indonesia" uses the Tessmer development model. From the results of expert validation, one to one trials, and field trials at PGMI UIN RF Palembang, it was found that the teaching materials developed were valid and effective. The effectiveness of the use of "Metodologi Pembelajaran Bahasa Indonesia" teaching materials can be seen in student learning outcomes. From the results of the evaluation, the mean value is greater than SKKNI, which is 83> 70 / C